Distribution and Interaction of Murine Pulmonary Phagocytes in the Naive and Allergic Lung - Hoffmann, Franziska M.; Berger, Johann L.; Lingel, Imke; Laumonnier, Yves; Lewkowich, Ian P.; Schmudde, Inken; König, Peter (Frontiers in Immunology, 2018)
The division of labor between pulmonary phagocytic subsets (macrophage/monocyte and DC subpopulations) has been described at the functional level. However, whether these lung phagocytes also display unique spatial distribution remains unclear. Here, to analyze cellular distribution in lung compartments and contacts between phagocyte subpopulations we established an immunohistochemistry (IHC)-based method to clearly identify murine lung phagocyte subsets in situ based on differential expression of CD11c, CD11b, MHC-II, Langerin and mPDCA-1. Further we investigated subset-specific functional differences in antigen uptake and spatial changes upon allergic sensitization. Our staining allowed the distinction between alveolar macrophages (AM), interstitial macrophage (IM) subpopulations, CD11b+ dendritic cell (DC) subpopulations, CD103+ DCs and plasmacytoid DCs (pDC). We identified interstitial regions between airways and around airways as regions of IM/CD11b+ DC/CD103+ DC clusters, where a subset of IMs (IM2) and CD103+ DCs formed intense contacts that decreased upon allergic sensitization. These data indicate functional interactions between both cell types either in steady-state or after antigen encounter affecting the development of allergies or tolerance. Further, we observed major antigen uptake in AMs and IMs rather than DC subpopulations that was no restricted to airways and adjacent areas. This will enable to focus future studies to immunologically relevant cellular interactions and to unravel which cells are tipping the balance between proinflammatory immune responses or tolerance.